2021
DOI: 10.1002/advs.202103248
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 N Protein Induces Acute Kidney Injury via Smad3‐Dependent G1 Cell Cycle Arrest Mechanism

Abstract: COVID‐19 is infected by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and can cause severe multiple organ injury and death. Kidney is one of major target organs of COVID‐19 and acute kidney injury (AKI) is common in critically ill COVID‐19 patients. However, mechanisms through which COVID‐19 causes AKI remain largely unknown and treatment remains unspecific and ineffective. Here, the authors report that normal kidney‐specifically overexpressing SARS‐CoV‐2 N develops AKI, which worsens in mice un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 60 publications
2
58
1
Order By: Relevance
“…As shown in Figure 9 , common hubs were predicted for each SARS-CoV-2 structural protein such as TGFB1/B3, SMAD and TEAD proteins, EGF, SPP1 and EDN1. It has been previously observed that SARS-CoV-2 N protein interacts with SMAD proteins enhancing TGF-beta signaling (Wang et al, 2022) whereas SARS-CoV-2 S protein triggers a transcriptional response associated to TGF-beta signaling (Biering et al, 2021). Interestingly, a therapeutic strategy focused on the inactivation of TGF-beta using integrin inhibitors has been proposed to mitigate COVID-19 severity (Huntington et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 9 , common hubs were predicted for each SARS-CoV-2 structural protein such as TGFB1/B3, SMAD and TEAD proteins, EGF, SPP1 and EDN1. It has been previously observed that SARS-CoV-2 N protein interacts with SMAD proteins enhancing TGF-beta signaling (Wang et al, 2022) whereas SARS-CoV-2 S protein triggers a transcriptional response associated to TGF-beta signaling (Biering et al, 2021). Interestingly, a therapeutic strategy focused on the inactivation of TGF-beta using integrin inhibitors has been proposed to mitigate COVID-19 severity (Huntington et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…AKI is also a common clinical feature in critically ill patients with COVID-19, particularly in those with inflammatory stress and underlying disease conditions 78 . Strikingly, our most recent study discovered that among SARS-CoV-2 proteins, SARS-CoV-2 N protein is pathogenic for AKI as kidney-specifically overexpressing SARS-CoV-2 N protein can directly induce AKI and promote severe AKI under ischemic conditions 79 . Mechanically, we uncover that SARS-CoV-2 N protein can bind and activate Smad3 signaling to trigger the p21-dependent cell death pathway via the G1 cell cycle arrest mechanism 79 , 80 .…”
Section: Regulatory Role and Mechanisms Of Smad3 In Cell Death During...mentioning
confidence: 98%
“…Strikingly, our most recent study discovered that among SARS-CoV-2 proteins, SARS-CoV-2 N protein is pathogenic for AKI as kidney-specifically overexpressing SARS-CoV-2 N protein can directly induce AKI and promote severe AKI under ischemic conditions 79 . Mechanically, we uncover that SARS-CoV-2 N protein can bind and activate Smad3 signaling to trigger the p21-dependent cell death pathway via the G1 cell cycle arrest mechanism 79 , 80 . Thus, targeting Smad3 by genic deletion of Smad3 or pharmacological inhibition of Smad3 signaling can protect against SARS-CoV-2 N-induced AKI 79 .…”
Section: Regulatory Role and Mechanisms Of Smad3 In Cell Death During...mentioning
confidence: 98%
See 1 more Smart Citation
“…Its failure is an important cause of patient death. In addition, kidney disease is a major contributor to patient death in a wide range of diseases such as diabetes, cancer, bacterial and viral infections (including COVID-19; Tang et al, 2021a ; Wang et al, 2021 ); leading to more than 6 million deaths worldwide each year. Thus, developing a better understanding, and treatment of, kidney disease is critical.…”
Section: Introductionmentioning
confidence: 99%